2020
DOI: 10.2147/ccide.s268527
|View full text |Cite
|
Sign up to set email alerts
|

<p>Direct Composite Resin for the Management of Tooth Wear: A Systematic Review</p>

Abstract: Background This study systematically reviewed survival of direct composite to restore worn teeth. Materials and Methods A comprehensive electronic search of databases sourced from Medline-PubMed, Embase, Cochrane Central, Scopus, Google scholar was performed on literature published between January 1990 and December 2018. Grey literature was also reviewed. Data extraction included sample size, number of composite restorations, operators, composite type, mean or total fol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…For that reason, resin composite was considered an ideal material for this patient's therapy, given its high resistance to acidic attack. The resin composite, applied with direct techniques, represented a straightforward and low-cost solution to treating worn dentitions, with satisfying functional and esthetic results [29].…”
Section: Discussionmentioning
confidence: 99%
“…For that reason, resin composite was considered an ideal material for this patient's therapy, given its high resistance to acidic attack. The resin composite, applied with direct techniques, represented a straightforward and low-cost solution to treating worn dentitions, with satisfying functional and esthetic results [29].…”
Section: Discussionmentioning
confidence: 99%
“…As a material, it has an acceptable survival probability in the shortto medium-term. 24 Although the restorations may fail at an increased rate, relative to a nonbruxing patient, this still represents a quick, cheap, biologically friendly and repairable treatment modality, even when failure is likely. Kassardjian and colleagues 25 have suggested that the annual intervention rate for direct composite restorations is 11.6%.…”
Section: Methodsmentioning
confidence: 99%
“…3,4,5,6,7,8 Each has its place, but this article will focus on the use of direct paste composite, which is perhaps the most evidence-based and adaptable of these materials. 9 Matrix transfer techniques (MTTs) are commonly used to directly convey planned information from a diagnostic wax-up (either analogue, digital or intra-oral mock-up) to a definitive restoration. The effective use of a MTT will improve the accuracy of the transfer, allowing predictable and efficient treatment.…”
Section: Introductionmentioning
confidence: 99%